The Innovative FEL design by the CompactLight Collaboration. Issue 1 (1st November 2022) - Gazis, N; Bignami, A; Trachanas, E; Alexopoulos, T; Telali, I; Apostolopoulos, T; Pramatari, K; Karagiannaki, A; Kotsopoulos, D; Gazis, E; Bandekas, D V
Abstract: The innovative FEL design by the CompactLight Collaboration is briefly presented. The major contribution of our team, mainly from Greece cooperating with the team of ESS-ERIC, is emphasised to the material selection of the proper photocathode illuminated with the relevant laser, the magnet and solenoid design of the injector for optimum beam conditions, the 3D CAD model design of the baseline FEL facility including the machine, the tunnel, the beam dump and the experimental hall. Additionally, the exploitation assets of the project with the transfer technology are presented.